ANALISIS PERILAKU KONSUMEN PERSPEKTIF EKONOMI ISLAM - Sarwono - (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRAK In economics terms, consumption is a human behavior to use goods and services for fulfill their needs. So, consumption is not only related to clotting and drinking, but the others economic behavior like buying and wearing a clothing, buying and riding a car, etc. In an Islamic perspectives, consumption behavior based on some assumption (Monzer Kahf): (1) Islam is the religion in society; (2) zakat is the obligation; (3) there are no riba in society; (4) mudharabah is implemented in business activities, and (5) consumer behavior is rational, that is to optimize utility. Key words: consumption, zakat, mudharabah, rational.